2014
DOI: 10.2478/mesbi-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for mesoporous silica nanoparticulate systems in facilitating biomedical applications

Abstract: Mesoporous silica nanoparticles (MSNs) have advanced to the forefront of multifunctional nanoparticulate systems in nanomedicine, owing to this highly fexible materials platform enabling a multitude of design options, often in a modular fashion. Drug delivery ability, detectability via diferent imaging modalities, and stimuliresponsiveness are often combined into one particle system. Very sophisticated and versatile designs along with impressive demonstrations of applicability have been reported to date, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 47 publications
8
68
0
Order By: Relevance
“…A boosting effect of FA on cellular uptake was only, but clearly, detected in the case when FA was linked to PEGylated particles where PEG was conjugated to the MSNs directly, without an intermediate PEI layer; and for which the basal uptake was thus, was low. All particles functionalized with PEI were internalized more efficiently than their counter-particle without PEI, in accordance with our previous studies 22,33 ( Figure S4A and B), and we have previously shown that this type of particles were internalized by the clathrin-mediated endocytosis route. 22 Particles without any polymeric coating or only modified with PEG showed low uptake probably associated with their almost neutral charge as well as tendency to aggregate at neutral conditions (Table 1).…”
supporting
confidence: 79%
See 4 more Smart Citations
“…A boosting effect of FA on cellular uptake was only, but clearly, detected in the case when FA was linked to PEGylated particles where PEG was conjugated to the MSNs directly, without an intermediate PEI layer; and for which the basal uptake was thus, was low. All particles functionalized with PEI were internalized more efficiently than their counter-particle without PEI, in accordance with our previous studies 22,33 ( Figure S4A and B), and we have previously shown that this type of particles were internalized by the clathrin-mediated endocytosis route. 22 Particles without any polymeric coating or only modified with PEG showed low uptake probably associated with their almost neutral charge as well as tendency to aggregate at neutral conditions (Table 1).…”
supporting
confidence: 79%
“…As the fluorescence intensity of fluorescein varies depending on the surrounding pH 38 as well as the particle functionalization regime 22,32 (Table 1), we detected the percent of cells which have internalized particles as a measure of uptake efficiency (Figure 2A). In Caco-2 cells, the cellular uptake was determined as a function of cell confluency.…”
Section: Msns Can Be Readily Internalized By Colon Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations